Cebuano fiction Sugilanong sugboanon - Alburo, Erlinda Kintanar; Bandillo, Vicente; Dumdum, Simeon R.; Mojares, Resil B. (Quezon City Ateneo de Manila University Press, 2009)
An anthology of prose fiction gathered from the mid-1800s until the year 2005. Each volume contains short stories or excerpts from short stories or novels in Cebuano.
[v. 1] Until 1940 -- [v. 2] 1941-2005.
In Cebuano and English.
Keywords: Cebuano fiction -- Collections; Cebuano fiction -- Translations into English; Philippine fiction (English) -- Translations from Cebuano; Short stories, Cebuano